HISTOMORPHOLOGICAL SPECTRUM OF ENDOSCOPIC BIOPSIES IN UPPER GASTROINTESTINAL LESIONS- A PROSPECTIVE STUDY. - Sandhya Kumari Sinha; Ragini Gupta (Student's Journal of Health Research, 2023)
Objectives: Upper gastrointestinal tract illnesses are among the most typical issues in clinical practice. Many diseases can affect the upper GIT. One of the key components of creating a successful treatment strategy is making a correct diagnosis of upper gastrointestinal problems, which necessitates histological confirmation. Identify the range of upper gastrointestinal tract histopathological lesions and establish endoscopic biopsies as a valuable tool for accurately diagnosing and treating a variety of upper gastrointestinal tract lesions. Materials & Methods:  The endoscopic biopsies of the upper GIT were the subjects of a prospective study, and the histological evaluation took place at the Department of Pathology at a tertiary care center for over a year. Results: 326 endoscopic biopsies from a total of 288 patients were examined. Patients who were men outnumbered patients who were women. A 9-88 age range was noted. There were cases involving the esophagus (18.4%), the GE junction (3.06%), the stomach (57.05%), the neo stomach (GJstoma), and the duodenum (20.85%). 20.24 percent of cases were benign neoplasms, 18.40 percent were malignant neoplasms, and 61.34 percent were non-neoplastic. The most often diagnosed inflammatory lesion, gastritis, was identified by histopathology as having 63 cases (63%), while the majority of the time identified malignant lesion, esophageal squamous cell carcinoma, had 19 instances (63.33%). Conclusion: In our study, 31.18% of neoplastic tumors and 69.89% of non-neoplastic lesions were found in the stomach (57%), which was also the most frequently used site for upper GI endoscopic biopsy. The most typical kind of stomach tumor is adenocarcinoma. Endoscopy enables the collection of biopsy samples from previously inaccessible sites without requiring a sizable resection. Recommendation: It is recommended to comprehend the variety of abnormalities that can be seen in these specimens to make the correct diagnosis and provide better patient treatment.